Montenegro : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2016)
This paper focuses on the important issues of Montenegro economy which are as follows: microfinancial setting, financial system resilience, financial oversight, resolution of nonperforming loans, and financial safety nets. Montenegro is still dealing with the aftermath of the collapse of the lending boom in 2008. Economic momentum has accelerated in 2015, but there are numerous downside risks. System-wide solvency and liquidity indicators appear broadly sound, but significant pockets of vulnerabilities exist among domestically owned banks. Decisive action to deal with weak banks is critical for preserving financial stability. While the legal, regulatory, and supervisory frameworks for banking and insurance sector have markedly improved since 2006 Financial Sector Assessment Program, further progress is required.